2014
DOI: 10.1016/j.fob.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle‐mediated transfer of long non‐coding RNA ROR modulates chemosensitivity in human hepatocellular cancer

Abstract: HighlightsSelected long non-coding RNA are aberrantly expressed in hepatocellular cancers.linc-ROR is a highly upregulated lncRNA that is expressed in response to TGFβ.linc-ROR contributes to chemoresistance of HCC cells.Intercellular transfer of linc-ROR occurs within extracellular vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
304
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(307 citation statements)
references
References 31 publications
2
304
1
Order By: Relevance
“…16 More importantly, exosomes-shuttling miRNAs probably conferred this resistance delivery. Followed by these studies, more and more evidence confirmed this observation in other cancers including breast cancer, prostate cancer, hepatocellular cancer, [17][18][19][20] and so on. However, similar to our previous study, most of these literatures mainly reported this phenomenon and few researchers 13 conduct in-depth study and systematically explore its detailed mechanism.…”
Section: Introductionmentioning
confidence: 65%
“…16 More importantly, exosomes-shuttling miRNAs probably conferred this resistance delivery. Followed by these studies, more and more evidence confirmed this observation in other cancers including breast cancer, prostate cancer, hepatocellular cancer, [17][18][19][20] and so on. However, similar to our previous study, most of these literatures mainly reported this phenomenon and few researchers 13 conduct in-depth study and systematically explore its detailed mechanism.…”
Section: Introductionmentioning
confidence: 65%
“…Exosomes contain a complex mixture of miRs, mRNAs, and proteins, and their ability to traverse the intercellular space and to be taken up by neighboring cells is becoming increasingly recognized as an important mechanism for delivering genetic, epigenetic, or proteomic information from donor cells and effecting functional modifications in recipient cells. 11,19,60,61 Whereas most previous studies have focused on these mechanisms as they relate to exosomal pathways in cancer and immune cells, including HCCs, 15,17,18 emerging evidence from this and other laboratories has revealed that fibrogenic cells are also regulated by exosomal networks. 10,22,23,31,34 In addition to revealing that miR-199a-5p targets the CCN2 3 0 -UTR in the same cells as which it is produced, the studies reported here indicate that miR199a-5p is released from HSCs in exosomes and that exosomal miR-199a-5p concentrations reflect those of their producer cells, being expressed at high levels in exosomes from quiescent HSCs and at low levels in exosomes from activated HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is plausible that EMT and expression of the stem cell markers induced by activation of the TGF-β pathway could be a predictor of unfavorable response of sorafenib in HCC. Another report has shown that the activation of TGF-β induces the expression of stress-responsive long non-coding RNA (lncRNA), which could impair chemotherapy-induced cell death and induce cells positive for the stem cell marker, CD133 [7]. Interestingly, sorafenib also induces stress-responsive lncRNA expression in treated cells [7], suggesting that acquisition of chemoresistance to sorafenib may involve the disruption of TGF-β, a stress-responsive lncRNA.…”
Section: Introductionmentioning
confidence: 99%